2014
DOI: 10.1126/scisignal.2004235
|View full text |Cite
|
Sign up to set email alerts
|

A Ligand-Independent VEGFR2 Signaling Pathway Limits Angiogenic Responses in Diabetes

Abstract: Although vascular complications are a hallmark of diabetes, the molecular mechanisms that underlie endothelial dysfunction are unclear. We showed that reactive oxygen species generated from hyperglycemia promoted ligand-independent phosphorylation of vascular endothelial growth factor receptor 2 (VEGFR2). This VEGFR2 signaling occurred within the Golgi compartment and resulted in progressively decreased availability of VEGFR2 at the cell surface. Consequently, the responses of endothelial cells to exogenous VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 55 publications
7
101
1
4
Order By: Relevance
“…In agreement to others (31), we also found that LPC transactivated VEGFR2, and that this transactivation, which did not require VEGF, was a key signaling pathway in the induction of LPC-induced permeability both in vitro and in vivo. Transactivation of VEGFR2 may thus occur within the cell, possibly through reactive oxygen species (32). Taken together, our data lend further support to the central role of VEGFR2 and its kinase activity in VEGF-dependent and independent vascular permeability.…”
Section: Discussionsupporting
confidence: 67%
“…In agreement to others (31), we also found that LPC transactivated VEGFR2, and that this transactivation, which did not require VEGF, was a key signaling pathway in the induction of LPC-induced permeability both in vitro and in vivo. Transactivation of VEGFR2 may thus occur within the cell, possibly through reactive oxygen species (32). Taken together, our data lend further support to the central role of VEGFR2 and its kinase activity in VEGF-dependent and independent vascular permeability.…”
Section: Discussionsupporting
confidence: 67%
“…El SRA, el VEGF-A y la nefrinuria fueron implicados en este proceso [18][19][20]22,[33][34][35][36][37][38] . Los podocitos y las células endoteliales en cultivo incrementaron la expresión de VEGF-A y de VEGFR2 en respuesta al aumento de glucosa [39][40][41] .…”
Section: Modificaciones Del Vegf-a Glomerular En La Ndunclassified
“…Warren y col. demostraron que en la diabetes la hiperglucemia disminuye la actividad del VEGFR2 endotelial 41 . La generación de ROS causada por la hiperglucemia, indujo activación del VEGFR2 y su posterior degradación, independientemente del VEGF-A 41 .…”
Section: Relación Entre El Vegf-a Y El óXido Nítrico En La Ndunclassified
“…In keeping with this, ROS generated from hyperglycemia promoted ligand-independent phosphorylation of vascular endothelial growth factor receptor 2 (VEGFR2). Hyperglycemia-induced phosphorylation of VEGFR2 did not require intrinsic receptor kinase activity and was instead mediated by Src family kinases [ 210 ].…”
Section: Redox-sensing Proteinsmentioning
confidence: 99%